Tropical Cyclone Frequency - Sobel, Adam H.; Wing, Allison A.; Camargo, Suzana J.; Patricola, Christina M.; Vecchi, Gabriel A.; Lee, Chia‐Ying; Tippett, Michael K. (Earth's future, 2021)
The frequency with which tropical cyclones (TCs) occur controls all other aspects of tropical cyclone risk since a storm that does not occur can do no harm. Yet this frequency is poorly understood. There is no accepted theory that explains the average number of TCs that occur each year on the Earth, nor how that number will change with global warming. Arguments based on global budgets of heat or moisture do not yet appear helpful, nor does a detailed understanding of the physical processes of TC genesis. Empirical indices that predict TC frequency as a function of large‐scale environmental variables can explain some of its relative variations in space and time, but not its absolute value. Global numerical models with horizontal grid spacings on the order of 25–50 km have allowed much improved simulations of TC activity, however. Many such models project a decrease in frequency with warming, but some project an increase. Idealized simulations, including those at higher resolutions, offer promise by allowing a systematic, deductive investigation of the roles of individual environmental factors. In addition to the larger‐scale environmental modulation of genesis likelihood, precursor disturbances, or “seeds”, may exert an independent influence on TC frequency. Plain Language Summary The term tropical cyclone frequency refers to the average number of tropical cyclones (also known as hurricanes, typhoons, etc.) which occur each year, either over the earth as a whole or in smaller regions. In this paper, the authors review the state of the science regarding what is known about tropical cyclone frequency. The state of the science is not great. There are around 80 tropical cyclones in a typical year, and we do not know why it is this number and not a much larger or smaller one. We also do not know much about whether this number should increase or decrease as the planet warms‐‐‐thus far, it has not done much of either on the global scale, though there are larger changes in some particular regions. No existing theory predicts tropical cyclone frequency. In this situation, we are left with numerical models as our primary tool, and the authors discuss the strengths, weaknesses, and different ways of using such models to investigate tropical cyclone frequency. Idealized simulations, in which the planet is made simpler than it really is, are allowing some new insights. Another promising avenue of investigation involves studying the weaker disturbances that sometimes strengthen into tropical cyclones. Key Points We do not understand why the number of tropical cyclones per year is what it is, nor how it may be changing In the absence of theory, our main tools are numerical models Promising research directions include idealized simulations at high resolution and study of precursor disturbances, or "seeds"